# Propositional maps

Content created by Egbert Rijke, Fredrik Bakke, Jonathan Prieto-Cubides, Daniel Gratzer and Elisabeth Stenholm.

Created on 2022-01-26.

module foundation.propositional-maps where

open import foundation-core.propositional-maps public

Imports
open import foundation.dependent-pair-types
open import foundation.embeddings
open import foundation.logical-equivalences
open import foundation.truncated-maps
open import foundation.universe-levels

open import foundation-core.equivalences
open import foundation-core.function-types
open import foundation-core.homotopies
open import foundation-core.propositions
open import foundation-core.truncation-levels


## Properties

### Being a propositional map is a property

module _
{l1 l2 : Level} {A : UU l1} {B : UU l2}
where

is-prop-is-prop-map : (f : A → B) → is-prop (is-prop-map f)
is-prop-is-prop-map f = is-prop-is-trunc-map neg-one-𝕋 f

is-prop-map-Prop : (A → B) → Prop (l1 ⊔ l2)
pr1 (is-prop-map-Prop f) = is-prop-map f
pr2 (is-prop-map-Prop f) = is-prop-is-prop-map f


### Being a propositional map is equivalent to being an embedding

module _
{l1 l2 : Level} {A : UU l1} {B : UU l2}
where

equiv-is-emb-is-prop-map : (f : A → B) → is-prop-map f ≃ is-emb f
equiv-is-emb-is-prop-map f =
equiv-iff
( is-prop-map-Prop f)
( is-emb-Prop f)
( is-emb-is-prop-map)
( is-prop-map-is-emb)

equiv-is-prop-map-is-emb : (f : A → B) → is-emb f ≃ is-prop-map f
equiv-is-prop-map-is-emb f =
equiv-iff
( is-emb-Prop f)
( is-prop-map-Prop f)
( is-prop-map-is-emb)
( is-emb-is-prop-map)


### Propositional maps are closed under homotopies

module _
{l1 l2 : Level} {A : UU l1} {B : UU l2} {f g : A → B} (H : f ~ g)
where

is-prop-map-htpy : is-prop-map g → is-prop-map f
is-prop-map-htpy = is-trunc-map-htpy neg-one-𝕋 H


### Propositional maps are closed under composition

module _
{l1 l2 l3 : Level} {A : UU l1} {B : UU l2} {X : UU l3}
(g : B → X) (h : A → B)
where

is-prop-map-comp : is-prop-map g → is-prop-map h → is-prop-map (g ∘ h)
is-prop-map-comp = is-trunc-map-comp neg-one-𝕋 g h

comp-prop-map :
{l1 l2 l3 : Level} {A : UU l1} {B : UU l2}
{X : UU l3} (g : prop-map B X) (h : prop-map A B) →
prop-map A X
pr1 (comp-prop-map g h) = pr1 g ∘ pr1 h
pr2 (comp-prop-map g h) =
is-prop-map-comp (pr1 g) (pr1 h) (pr2 g) (pr2 h)


### In a commuting triangle f ~ g ∘ h, if g and h are propositional maps, then f is a propositional map

module _
{l1 l2 l3 : Level} {A : UU l1} {B : UU l2} {X : UU l3}
(f : A → X) (g : B → X) (h : A → B) (H : f ~ (g ∘ h))
where

is-prop-map-left-map-triangle :
is-prop-map g → is-prop-map h → is-prop-map f
is-prop-map-left-map-triangle =
is-trunc-map-left-map-triangle neg-one-𝕋 f g h H


### In a commuting triangle f ~ g ∘ h, if f and g are propositional maps, then h is a propositional map

module _
{l1 l2 l3 : Level} {A : UU l1} {B : UU l2} {X : UU l3}
(f : A → X) (g : B → X) (h : A → B) (H : f ~ (g ∘ h))
where

is-prop-map-top-map-triangle :
is-prop-map g → is-prop-map f → is-prop-map h
is-prop-map-top-map-triangle =
is-trunc-map-top-map-triangle neg-one-𝕋 f g h H


### If a composite g ∘ h and its left factor g are propositional maps, then its right factor h is a propositional map

module _
{l1 l2 l3 : Level} {A : UU l1} {B : UU l2} {X : UU l3}
(g : B → X) (h : A → B)
where

is-prop-map-right-factor :
is-prop-map g → is-prop-map (g ∘ h) → is-prop-map h
is-prop-map-right-factor =
is-trunc-map-right-factor neg-one-𝕋 g h


### A -1-truncated map is k+1-truncated

abstract
is-trunc-map-is-prop-map :
{l1 l2 : Level} (k : 𝕋) {A : UU l1} {B : UU l2} {f : A → B} →
is-prop-map f → is-trunc-map (succ-𝕋 k) f
is-trunc-map-is-prop-map neg-two-𝕋 H = H
is-trunc-map-is-prop-map (succ-𝕋 k) H =
is-trunc-map-succ-is-trunc-map (succ-𝕋 k) (is-trunc-map-is-prop-map k H)